Lactose reduced ice cream enriched with whey powder - Ana Claudia Tsuchiya (Semina: Ciências Agrárias, 2017)
Ice cream is a food product that pleases the palate of consumers worldwide. Whey powder (WP) has various technological and functional properties. However, WP increases the lactose content of the final products in which it is incorporated and causes grittiness and intolerance in lactose-sensitive individuals. This study aimed to produce ice cream with milk powder (MP) replaced by WP (MP/WP), decrease the lactose content by enzymatic hydrolysis and verify the physicochemical and microbiological parameters of the final product. Initially, the variables ?-galactosidase concentration and reaction time were studied for the response of the percentage of lactose hydrolysis in a milk ice cream base, using a full 22 factorial design(FFD).With the reaction conditions defined (0.5 g L-1 of ?-galactosidase at 37 C for 4 h)the sucrose concentration and MP/WP replacement variables were then studied in the ice cream formulation for the percentage of lactose hydrolysis and overrun responses using a 22 FFD. The lactose hydrolysis, which ranged between 86.59-97.97%, was not affected by the MP/WP replacement in the ice cream, whilst the overrun was increased by the MP/WP replacement. The physicochemical and microbiological parameters of the ice cream were either not influenced or positively influenced by lactose hydrolysis and MP/WP replacement.